Assessing tax inspection performance - DE CARVALHO COUY, Joao Paulo (KDI School, 2015)
The search for operational efficiency has caused a series of organizational changes for the Secretariat of the Federal Revenue of Brazil (RFB). A large number of them are taking place on tax inspection projection, whose activities have been shifted to regional groups. As the restructure trend seems to only be beginning, it is necessary to evaluate the performance of the current structure in order to guide the forthcoming changes. The present thesis makes use of Data Envelopment Analysis to rank local offices according their tax inspection performance. The study identified the potential outputs that were not achieved, the best and worst performing units, as well as the relation between their performance and geographic characteristics.
Thesis(Master) --KDI School:Master of Public Policy,2015